Conditional Love: Threat and Attitudinal Perceptions of Immigrants Depend on Their Instrumentality to Locals' Basic Psychological Needs. (December 2021) - Yong, Jose C.; Jia, Lile; Ismail, Ismaharif; Lee, Peiwei
Although threat perceptions are commonly used to explain attitudes toward immigrants, the psychological factors underlying threat are surprisingly understudied. Drawing from goal pursuit and self-determination theory, we examined the perceived instrumentality of immigrants as an antecedent of locals' threat and attitudinal perceptions. Through four studies ( N = 1, 372) with different configurations of local population segments and target immigrant groups, we investigated the impact of immigrants' instrumentality in terms of hindrances to locals' autonomy, belonging, and competence needs. Including hindrances to our proposed model of threats and attitudes led to an improvement in the overall fit with the data, allowed for a better specification of the threats-to-attitudes pathways, and elucidated the complexity and downstream consequences (endorsement of pro-immigration policies) of attitudes. The present findings underscore the utility of goal-driven approaches to studying intergroup conflicts, and implications for understanding and improving locals' attitudes toward immigrants are discussed.